AL-KHILÂFAH MENURUT AL-MÂWARDY: PENDEKATAN SOSIO-HISTORIS - 'Irfaan, Santosa (PKn Progresif, 2008)
The absence of Muhammad?slast messages before his death related to the continuation of Moslem?s leader aroused the ijtihâd of al-khilâfah. In the end of 10 th century or at the beginning of 11 th century, al-Mâwardy came with great ideas on khilâfah. It consist of qualification and the process of choosing leader (khalîfah), duties that should be done by khalîfah as and individu and as social responsibilities to the society. His great knowledge abouth Fiqh al-Siyâsah (Islamic political), his ability on writing, his experiences as judge, and his ability on negotiation made him accepted by many people. It was also supported by his attitude; srtick, moderate, and brave, his intelligence proved by his skill and his good behaviour.